2020
DOI: 10.1158/0008-5472.can-19-1532
|View full text |Cite
|
Sign up to set email alerts
|

HIF2-Induced Long Noncoding RNA RAB11B-AS1 Promotes Hypoxia-Mediated Angiogenesis and Breast Cancer Metastasis

Abstract: Hypoxia induces a vast array of long noncoding RNAs (lncRNA) in breast cancer cells, but their biological functions remain largely unknown. Here, we identified a hitherto uncharacterized hypoxiainduced lncRNA RAB11B-AS1 in breast cancer cells. RAB11B-AS1 is a natural lncRNA upregulated in human breast cancer and its expression is induced by hypoxia-inducible factor 2 (HIF2), but not HIF1, in response to hypoxia. RAB11B-AS1 enhanced the expression of angiogenic factors including VEGFA and ANGPTL4 in hypoxic bre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
106
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(110 citation statements)
references
References 28 publications
4
106
0
Order By: Relevance
“…Metastasis and angiogenesis are typical characteristics of breast cancer, which lead to poor prognosis, frequent recurrence and pronounced invasiveness [17]. Accumulating evidence has revealed that lncRNAs play an important role in the carcinogenesis and progression of breast cancer by in uencing critical events such as cell proliferation, metastasis, and angiogenesis [18]. In the present study, we rstly gured out a novel lncRNA PCDHB17P, which was highly expressed in breast cancer tissues and also associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 72%
“…Metastasis and angiogenesis are typical characteristics of breast cancer, which lead to poor prognosis, frequent recurrence and pronounced invasiveness [17]. Accumulating evidence has revealed that lncRNAs play an important role in the carcinogenesis and progression of breast cancer by in uencing critical events such as cell proliferation, metastasis, and angiogenesis [18]. In the present study, we rstly gured out a novel lncRNA PCDHB17P, which was highly expressed in breast cancer tissues and also associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 72%
“…Previous studies have reported that in colorectal cancer, the novel primate‐specific lncRNA FLANC not only affects tumor growth but also participates in angiogenesis by regulating the STAT3/VEGF‐A axis 37 . In breast cancer lncRNA RAB11B‐AS1 was reported to be induced under hypoxia and facilitate the expression of angiogenic factors (eg, VEGF‐A and ANGPTL4) in breast cancer cells by facilitating recruitment of RNA polymerase II, leading to angiogenesis and metastasis in breast cancer 38 . Furthermore, regarding the relationship between p21 and vascular endothelial growth factor A (VEGF‐A), it was observed that when p21 levels increased, VEGF‐A expression decreased 39 .…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA ZFAS1 promotes angiogenesis via miR-150-5p/VEGFA signaling [165]. In breast cancer cells, lncRNA RAB11B-AS1 recruits RNA polymerase II to upregulate VEGFA and ANGPTL4 expression and promotes tumor angiogenesis [166]. In hepatocellular carcinoma cells, lncRNA HULC promotes angiogenesis via miR-107/E2F1/SPHK1 signaling [167].…”
Section: Non-coding Rnamentioning
confidence: 99%